THE EFFECT OF CONSUMERS' PERCEPTIONS OF PRODUCT/SERVICE QUALITY ON THEIR BUYING BEHAVIOR: THE MEDIATING ROLE OF BRAND LOVE - TEKİN, Mahmut; GÖBENEZ, Yılmaz; ÖZTÜRK, Derya (SSD Journal, 2022)
Brand love is the sum of the values that turn into desire and passion with the pleasure, enthusiasm, and excitement that a consumer experiences when using a product or service. This passion turns into brand love over time, whether the consumer is aware of it or not. Brand love is full of surprises, just like the love people have for each other. This element of surprise is about the change in the feeling that reveals love in us and keeps it alive. This change in feeling is related to the quality that creates love depending on fashion, innovation, products, services, time, and trust in a brand. In this context, this study aimed to determine whether brand love played a mediating role in the effect of consumers' perceptions of the quality of products or services on their buying behavior. The sample consisted of 384 brand X car users living in Turkey. Participants were recruited using convenience sampling. Data were collected using an online survey. Hypotheses were tested using linear and multiple regression analysis. The mediating role of brand love was determined using the four steps in Baron and Kenny's method (1986), while the significance of the indirect effect was tested using the Sobel test. The results showed positive and significant relationships between product/service quality, brand love, and buying behavior. The results indicate that brand love plays a partially mediating role in the effect of consumers' perceptions of product/service quality on their buying behavior. In the light of these findings, the product/service quality perceived by consumers for automobile brands affects their buying behavior through brand love.